Notary Liability When Committing Disgraceful Acts - Islamianiati, Andina Arityas; Mahfud, Muh Afif (Universitas Islam Sultan Agung, 2023)
Disgraceful acts are regulated in Article 9 paragraph 1 letter c of Act No. 2 of 2014 concerning the Office of a Notary. Disgraceful acts are degrading honor and dignity, such as gambling, drinking, using drugs and adultery. Meanwhile, disgraceful acts are those who have committed acts that are not in accordance with existing norms in Indonesia such as religious norms, decency and customs. The purpose of this research is to find out what are the types of dismissal of a notary and how is the responsibility of a notary who has committed a disgraceful act. The research method used is normative juridical research. The source of legal material used by the author is secondary data. The result of the research is that a Notary who is caught committing a violation of a disgraceful act as stated in Article 9 paragraph 1 letter C of Act No. 2 of 2014 Concerning Notary Positions, the board of trustees decides for the notary to be temporarily dismissed for 6 months based on the Notary Office Law.